2015
DOI: 10.1007/s00066-015-0829-z
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel, cisplatin and 5-fluorouracil induction chemotherapy followed by chemoradiotherapy or chemoradiotherapy alone in stage III–IV unresectable head and neck cancer

Abstract: The addition of ICT to CRT did not show any advantage in our phase II trial, while the incidence of adverse events increased. The three deaths as a consequence of ICT call attention to the importance of adequate patient selection if ICT is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 17 publications
0
43
1
Order By: Relevance
“…18,19 The 3-year overall (43% vs 55%) or progression-free (41% vs 50%) survival rates were not significantly different in the induction CT with docetaxel + CCRT and CCRT groups. 19 PARADIGM and DECIDE were phase III trials that were closed to accrual and did not fulfill the predicted accrual targets.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…18,19 The 3-year overall (43% vs 55%) or progression-free (41% vs 50%) survival rates were not significantly different in the induction CT with docetaxel + CCRT and CCRT groups. 19 PARADIGM and DECIDE were phase III trials that were closed to accrual and did not fulfill the predicted accrual targets.…”
Section: Discussionmentioning
confidence: 91%
“…18,19 The 3-year overall (43% vs 55%) or progression-free (41% vs 50%) survival rates were not significantly different in the induction CT with docetaxel + CCRT and CCRT groups. 19 PARADIGM and DECIDE were phase III trials that were closed to accrual and did not fulfill the predicted accrual targets. In both trials, docetaxel-based induction CT did not improve survival; 7,8 however, a randomized phase II trial by Paccagnella et al 20 demonstrated that adding docetaxel-based induction CT to CCRT increased the rate of complete radiological response compared with CCRT alone, and the trend favored progression-free and overall survival after docetaxel inclusion.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…According to the latest research, though novel surgical treatments, chemotherapy drugs, more advanced radiotherapy means and targeted drugs have been applied in treating laryngocarcinoma in the last 30 years, the overall survival of patients with laryngocarcinoma has not improved, instead, it even shows a decreasing trend, which is ~50%; and that of advanced stage laryngocarcinoma is even as low as 30-40%. The overall therapeutic effects are unsatisfying (3).…”
Section: Introductionmentioning
confidence: 99%